ANALISIS TINGKAT KEPUASAN MAHASISWA ATAS KUALITAS PELAYANAN LAYANAN ADMINISTRASI MAHASISWA UNIVERSITAS BUNDA MULIA, JAKARTA - William Darius; Arko Pujadi (Business Management Journal, 2017)
The purpose of this research is to find out about the difference between expectation of University of Bunda Mulia students and the performance of Layanan Administrasi Mahasiswa performances.This research is descriptive research. The method of sampling is non probability sampling and the technique is purposive sampling. The sample consists of 100 respondent that obtained from Bunda Mulia University students in odd semester period 2009/2010. The result of this research shows that Bunda Mulia University students feel satisfy with Layanan Administrasi Mahasiswa service after compare Layanan Administrasi Mahasiswa performances with Bunda Mulia University student’s expectation. Keyword : Service quality, Satisfaction, Performances